Seismic Tomography in Reykjanes , SW Iceland - Jousset, Philippe (author); Blanck, Hanna (author); Franke, Steven (author); Metz, M. (author); Águstsson, K. (author); Verdel, Arie (author); Ryberg, T. (author); Hersir, Gylfi Páll (author); Weemstra, C. (author); Bruhn, D.F. (author); Flovenz, Olafur G (author) (2016)
We present tomographic results obtained around geothermal reservoirs using seismic data recorded both on-land Reykjanes, SW-Iceland and offshore along Reykjanes Ridge. We gathered records from a network of 83 seismic stations (including 21 Ocean Bottom Seismometers) deployed between April 2014 and August 2015. We obtain crustal velocity images from several tomography methods. First, we used local earthquakes to perform travel time tomography. The processing includes first arrival picking of P- and S-phases using an automatic detection and picking technique based on Akaike Information Criteria. We locate earthquakes by using a non-linear localization technique, as a priori information for deriving a 1D velocity model. We then computed a 3D velocity model by joint inversion of each earthquake’s location and velocity lateral anomalies with respect to the 1D model. Our results confirms previous models obtained in the area, with enhanced details. Second, we used ambient noise cross-correlation techniques which involve the computation of cross-correlation between seismic records. Empirical Green’s functions are estimated and analyzed to derive an S-wave velocity model by surface wave tomography. Third, noise correlation theory shows that zero-offset P-wave reflectivity at selected station locations can be approximated by auto-correlating and stacking station data. With few assumptions, single-station autocorrelations provide local 1D high-resolution structural acoustic-contrast versus depth information. We show that the application of ambient noise interferometry for reflection retrieval complement well the results from both classical and noise tomography methods. Applied Geophysics and Petrophysics Reservoir Engineering